2019
DOI: 10.1063/1.5097411
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the impact of atomic- and nano-scale indium distributions on the optical properties of InGaN/GaN quantum well structures grown on m-plane freestanding GaN substrates

Abstract: Insight into the impact of atomic-and nano-scale indium distributions on the optical properties of InGaN/GaN quantum well structures grown on m-plane freestanding GaN substrates. Journal of Applied Physics, 125(22), [225704].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Indeed, atom probe tomography (APT) has shown that most InGaN alloys are random alloys . For indium compositions exceeding x = 0.14, a recent APT study reported that the distribution of indium atoms in InGaN can deviate from being truly random and lead to clusters of indium atoms . Our calculations of defects in different configurations for a given In composition allow us to comment on how the coordination of In atoms around an impurity affects the formation energy E f .…”
Section: Resultsmentioning
confidence: 87%
“…Indeed, atom probe tomography (APT) has shown that most InGaN alloys are random alloys . For indium compositions exceeding x = 0.14, a recent APT study reported that the distribution of indium atoms in InGaN can deviate from being truly random and lead to clusters of indium atoms . Our calculations of defects in different configurations for a given In composition allow us to comment on how the coordination of In atoms around an impurity affects the formation energy E f .…”
Section: Resultsmentioning
confidence: 87%
“…These are important elements for the interpretation of the carrier localization mechanisms -and thus for the explanation of the radiative efficiency -within these quantum confined emitters that constitute the active region of standard LEDs [3]. Other statistical studies have pointed out that the (In,Ga)N behavior is different in quantum wells grown on non-polar planes, on which In clustering becomes possible [4][5]. However, there are many other examples of statistical correlation in the literature, not only on wide bandgap semiconductors [6], but also on semiconductor nanoparticles within insulating matrices [7][8][9] and on III-V nanowires [10].…”
Section: Correlative Methods With Optical Spectroscopymentioning
confidence: 99%